Internalisasi Nilai-Nilai Aswaja An-Nahdiyah dalam Pembelajaran di Pondok Pesantren Salafi Sunanul Huda Kabupaten Sukabumi - Cacang Cacang; Nurdin Nurdin; Amin Abdillah; Imam Asrofi; Ramdani Sutrisna; Meri Noviyanti; Salwaa Fatihah Mumtahanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to thoroughly examine the triadic relationship among the Internalization of Aswaja An-Nahdliyah Values, the Pedagogic Competence of Ustadz/Ustadzah, and the Academic Supervision by the Kyai at the Salafi Sunanul Huda Islamic Boarding School in Sukabumi Regency. The research urgency is based on the vital role of the pesantren (Islamic boarding school) as a fortress of moderate ideology and the existence of a research gap that has not holistically integrated these three variables within the specific Salafi-Nahdliyyah context of the locus. The Aswaja An-Nahdliyah values central to the internalization process include Tawasuth (moderation), Tasamuh (tolerance), I'tidal (justice/firmness), Tawazun (balance), and Amar Ma'ruf Nahi Munkar (enjoining good and forbidding wrong). This internalization is carried out through the formal curriculum (teaching Kitab Kuning using the Sorogan and Bandongan methods) and the non-curricular aspects (Kyai/Ustadz role-modeling and pesantren living values). The study utilizes a qualitative approach with a Case Study design. Data collection employs Method Triangulation involving In-depth Interviews (Kyai, Ustadz, Students), Limited Participatory Observation (learning processes and cultural activities), and Document Study (Lesson Plans, curriculum, and supervision reports). Data analysis employs the interactive model of Miles, Huberman, and Saldana (Data Condensation, Data Display, and Conclusion Drawing). The research findings are expected to formulate the Integrated Model of Triguna Santri in Aswaja An-Nahdliyah Internalization, which synergizes traditional pesantren methods with culture-based quality assurance. Practically, these findings will provide blueprints for quality assurance (Cultural-Authoritative Academic Supervision) and recommendations for pedagogical strategies for Ustadz/Ustadzah to enhance the transfer of values from the cognitive level to the affective and behavioral domains. This model is expected to become a benchmark for developing educator competence and strengthening religious moderation in similar pesantren.